Fabrication and characterization of novel hollow fiber catalytic packing of PFSA–PES–ZrO2 (shell)–TiO2 (core) solid superacid via wet-spinning method. (2nd October 2016) - Ji, Chen-Hao; Xue, Shuang-Mei; Xu, Zhen-Liang; Ma, Xiao-Hua
Abstract: In this work, a novel hollow fiber catalytic packing (HFCP) was fabricated of ZrO2 (shell)/TiO2 (core) (TZ) solid superacid nanoparticles, perfluorinated sulfonic acid resin (PFSA) and polyethersulfone (PES) via wet-spinning method. TZ was a homemade binary solid superacid nanoparticles with core–shell structure using superfine titania (5 nm) as the core and mesoporous tetragonal phase zirconia as the shell. It was synthesized through the hydrolysis of zirconium oxychloride in the presence of titania nanoparticles and cetyltrimethylammonium bromide (CTAB) hexagonal crystals covered on the titania core and followed by calcination and acidification. HFCPs demonstrated well catalytic performance in the esterification test of ethanol and acetic acid due to the superacid sites on the surface of TZ and PFSA polymer chain. And the superacid sites on the PFSA polymer chain could be sufficiently exposed by the embedding of the nanoparticles. At the same time, HFCPs also showed ultrahigh recovery which was more than 99.5% in 6 runs because of the well integrality benefited from the wet-spinning method. The specific surface area (SSA) and pore size distribution were analyzed by N2 adsorption–desorption, the result showed that the SSA of HFCPs decreased with the increasing of the PFSA additive amount. The SSA of the HFCP with the best catalytic performance could be up to 90.60 m 2 /g, in which the PFSA weight proportion was 13%. The XRD pattern and HRTEM image showed the HFCPs i.e. the zirconia shell of TZ formed uniform tetragonal phase. Other characterizations such as FT-IR, XPS, SEM and TEM were utilized to determine the chemical composition and morphology of the HFCPs and TZ, the results showed the novel catalytic packing was a suitable catalyst for the acid catalyzed reactions. Graphical abstract: Highlights: PFSA–PES–ZrO2 (shell)–TiO2 (core) HFCP demonstrated well catalytic performance. Well integrality of the HFCPs benefited from the wet-spinning method. Sufficient exposure of the acid sites on PFSA by the nanoparticles. Uniform tetragonal phase formed on the zirconia shell of TZ.